2022
DOI: 10.3389/fpls.2022.959427
|View full text |Cite
|
Sign up to set email alerts
|

Salt-tolerant endophytic bacterium Enterobacter ludwigii B30 enhance bermudagrass growth under salt stress by modulating plant physiology and changing rhizosphere and root bacterial community

Abstract: Osmotic and ionic induced salt stress suppresses plant growth. In a previous study, Enterobacter ludwigii B30, isolated from Paspalum vaginatum, improved seed germination, root length, and seedling length of bermudagrass (Cynodon dactylon) under salt stress. In this study, E. ludwigii B30 application improved fresh weight and dry weight, carotenoid and chlorophyll levels, catalase and superoxide dismutase activities, indole acetic acid content and K+ concentration. Without E. ludwigii B30 treatment, bermudagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…In addition, future research should include a recovery component after salinity stress to provide more details for consumers regarding a specific turfgrass cultivar’s recuperative capacity to salinity stress. As prior studies have indicated, exogenous applications of various chemical products such as PGRs, silicon, various external applicants ( Table 3 ), and even biological agents have elevated abiotic stress resistance and improved carbohydrate metabolism while under stress for many salt-sensitive turfgrass species [ 108 , 123 , 127 ]. There is still a need for further research on optimal turfgrass nutrition and nutrition homeostasis before and during salinity stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, future research should include a recovery component after salinity stress to provide more details for consumers regarding a specific turfgrass cultivar’s recuperative capacity to salinity stress. As prior studies have indicated, exogenous applications of various chemical products such as PGRs, silicon, various external applicants ( Table 3 ), and even biological agents have elevated abiotic stress resistance and improved carbohydrate metabolism while under stress for many salt-sensitive turfgrass species [ 108 , 123 , 127 ]. There is still a need for further research on optimal turfgrass nutrition and nutrition homeostasis before and during salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Both fungal and bacterial endophytes typically colonize and live within an individual host plant throughout its life cycle without causing any significant parasitic symptoms as symbiotic relationships. Among turfgrasses, several species have been identified to mitigate salinity stresses [ 127 ]. The mechanisms are highly related to the host plant water and nutrient uptake, and enhanced plant hormone productions to minimize salinity, drought, and heat stresses.…”
Section: Management Practices To Improve Turfgrass Salinity Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In early Studies numerous plant species have been treated with endophytic bacteria to reduce salt stress ( Pal et al., 2021 ; Sofy et al., 2021 ). Similarly, the inoculation of E. ludwigii B30 improved plant growth in both non-salt stress and salt stress environments, as evidenced by higher shoot height, root length, and shoot and root biomass ( Wei et al., 2022 ). The antioxidative enzymes produced by PGPB or the expression of plant genes involved in the synthesis of ROS-scavengers can both help plants recover from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by other researchers who used the salt-tolerant endophytic bacterium Enterobacter ludwigii B30 to increase fresh and dry weights; carotenoid and chlorophyll contents; catalase and superoxide dismutase activities; indoleacetic acid contents; and K + concentration. Without the E. Ludwigii B30 treatment, the malondialdehyde, proline, PSII [Y (NO) and Y (NPQ)], 1-aminocyclopropane-1-carboxylic acid, and abscisic acid contents of dogbanes decreased under salt stress [85].…”
Section: Accumulation Of Plant Hormonesmentioning
confidence: 99%